The sense of systemization practice in higher education - Silva Ortiz, Sara Raquel (Universidad Pedagógica y Tecnológica de Colombia, 2012)
In higher education the systemization is not merely conceptualized and characterized as a proposal derived from the typical methodologies of scientific research, but it is spread as a formal and rigorous process of categorization, mediated by the reflection on the daily experiences developed in the educational field. This reflection process gives a new concerted and contextualized meaning to the gained experience, by transforming the practices and the realities knowledge arises from. Therefore, systemization practice, understood as a reflection process, becomes significantly valid and makes possible for itself to go from the experience to the production of ongoing knowledge, open to de– construction, and faced up to the reality of this practice. This reflection paper reviews the theoretical and epistemological basis concerning the systemization of practices and presents the systemization proposal for an educational experience related to Anatomy teaching, mediating with a didactics alternative, i.e., Problem Based Learning (PBL). Thus, this proposal is a useful opportunity for analyzing and reflecting on pedagogical practices determined by teaching experience in interaction with action subjects